Eksistensi Perbankan Syariah di Indonesia - Imroatus Sholiha (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2018)
This article aims to find out the existence of Islamic banking in Indonesia, This research uses qualitative descriptive research method. In this descriptive qualitative research, the researcher uses literature study which is searching information through books, magazines, journals, SPS OJK date, reference books, and other sources either in written form or in relevant digital format and related to research study object. The results of this study show that sharia banking first started to enter Indonesia in 1992 pioneered by Bank Muamalat Indonesia (BMI) until now its existence still exist and develop rapidly. Visible from year to year the number of sharia banking office experienced a rapid growth yaiitu increasing number of offices spread throughout the province in Indonesia both Sharia (BUS), Syariah Business Unit (UUS) and BPRS. For the branch network of BUS and UUS in 2016 for KPO / KC as much as 623, KCP/UPS as many as 1,342 and KK as many as 240. While the number of BPRS in Iindonesia in 2012 as many as 158 and increased in 2016 to 166. So is the number of customers who save money and take the number of pembisiyaan increasingly increasing year in 2014 the number of customers BUS Dan UUS as much as 11,444,013 and increased in 2016 to 18. 521.121. As for the number of accounts both DPK and Financing also increased from year to year. For the DPK of 2014 the number is 14,386,575 and increased in 2016 to 22. 198.718, and for financing, receivables and greetings in the year 2014 amounted to 3. 769,181 in 2016 increased to 4,515,930.